Vozes subalternas em meio à multidão: na encruzilhada de Linn da Quebrada - Diego Aparecido Cafola (2021)
Through her artistic production and by media occupation, Linn da Quebrada makes explicit the markers of difference that operate in her subjectivation and in her social experience, which is crossed by the lives of many other travestis and by the peripheral music scene. In her works, the artist relates these markers to each other and, based on them, Linn causes tension to the Brazilian hegemonic culture. As a subject, Linn is distant from the midpoint and at the edge of some rules normalized by the group centralized on the contemporary western hegemony. This group is characterized by being white, bourgeois and hetero-cis-normative. Linn introduces herself as a queer transvestite subject – a bixa travesti –, a black, peripheral artivist and a gender terrorist. A multi atroz, actress of atrocity, as she entitled herself. Based on her discursive practice, this essay questions what tensions are caused in relation to the mechanisms of power that operate the normalization of the subalternized individual in Brazilian hegemonic culture. The objective is to analyze discursive practices of Linn da Quebrada considering the intersection of race, social class, sex and gender that crosses her discourse and her first art production space, the Brazilian funk. This essay examines themes that take place in the artistic work of Linn, such as invisibility, precariousness and violence, together with the markers of difference of this dissident body, in dialogue with queer and decolonial consideration. To this end, an exploratory research was conducted in databases and in media production about Linn da Quebrada. Furthermore, a field notebook and data quantification are added to the use of YouTube platform to create a virtual ethnography of this artivist. These strategies were carried out in order to understand, among other things, what are the main tensions that Linn puts into question by not recognizing herself within the borders of the hegemonic norm.